Conscientious objection as an exempt of criminal responsability in Colombia (2018)
Conscientious objection is one of the most studied topics in the foreign constitutional literature in recent years, which, however, in our environment is almost non-existent. In Colombia, it has not been analyzed in depth its possible treatment as a cause